The relationship between aggressive behaviors of preschool children and the violence against Iranian women in the COVID-19 pandemic - Neda Asadi; Fatemeh Salmani; Mahin Salmani (BMC, 2022)
Abstract Background During epidemics, supports are limited and individual and collective vulnerabilities as well as domestic violence are increased. Therefore, various groups in society, especially children and their mothers, are extremely vulnerable. This study aimed to assess the relationship between aggressive behaviors of preschool children and the violence against Iranian women during the COVID-19 pandemic. Methods This descriptive-correlational study was conducted in October-November 2020. Stratified random sampling was performed among preschool children in Kerman. Data were collected using the Violence toward Women Inventory and the Aggression scale for preschoolers Scale. Data were analyzed using SPSS25, ANOVA, independent t-test, and Pearson correlation test. Results The results showed that the total mean scores of violence against women and preschoolers' aggression were 54.43 ± 10.6 and 88.44 ± 6.5, respectively. The results showed a statistically significant difference in aggressive behaviors of preschool children, mother's job, number of children, mother's education, income, and age. A positive and significant relationship was also found between the subscales of violence against women and aggression in preschool children. Conclusions The results showed a positive and significant relationship between violence against women and aggression of preschool children. Therefore, it is recommended that parents identify and eliminate the risk factors for domestic violence during the COVID-19 in order to protect their children. Parents also must learn coping strategies for stress and resilience in the epidemic crises.